Dampak Kesehatan Mental pada Lansia selama Pandemi COVID-19 Telaah Pustaka - Yosi Duwita Arinda; Nur Khotimah Elfiyani; Nurmalia Lusida; Hadi Pratomo (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Since December 2019, the world has faced challenges of the Coronavirus-19 disease (COVID-19). It is a severe infectious disease caused by the new coronavirus, SARS-CoV-2. Both the elderly groups and individuals with comorbid were most at risk of contracting this disease. They could experience severe symptoms and even death. Objective: To examine psychological health problems among the elderly during the COVID-19 pandemic. Methods: This study was a review of the literature contained in the database of health journals, namely SpringerLink, Science Direct, ProQuest, and Pubmed. Selected papers based on free full text, open access, in English, and were published during 2020-2021. Results: They were 13 articles included in the review. Eleven (11) studies reported that the COVID-19 pandemic indicated psychological among the elderly group, such as increased symptoms of anxiety, depression, and feelings of loneliness. On the contrary, 2 studies showed lower anxiety, depression, and loneliness among the elderly, requiring further research evidence. Conclusion: The COVID-19 pandemic did psychological impact to the elderly. The results did not show uniform results. Therefore, further research is suggested.